Game Model Based on Environment Insights for Elementary School Children (6-12 Years) - Marlinda Budiningsih; Nofi Marlina Siregar; Hernawan Hernawan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to create a product in the form of a game model based on environmental insights for elementary school children. This research is a research development using research and development from Borg and Gall which consists of ten steps. In this study, researchers only used eight steps because after conducting a small group trial and product evaluation it was declared to be feasible for a primary trial or field trial by experts. This study involved 80 subjects aged 6-12 years. Data collected through observation, interviews, and tests.The significant value of the difference in the results of t-count = 28,971, and p-value = 0.00 <0.05, which means there is a significant difference in understanding of environmental insights before and after being treated in the form of a game model based on environmental insights. It was concluded that the game model developed was effective in increasing understanding of environmental knowledge for children aged 6-12 years.